Urban growth and liberal fixation on the land in a sustainable city context in greater Lomé (Togo) - Adjayi, Komi Arsène Fulbert; Kpotchou, Koffi; Nassi, Karl Martial; Atchon, Kodjo Sena; Gbekley, Efui Holaly (Edelweiss Applied Science and Technology, 2024)
Over the last two decades, greater Lomé has experienced a spatial evolution marked by a disproportionate fixation of Lomé residents on the ground. This liberal occupation of urban land undermines the development of the capital and delays the vision of a sustainable city initiated by the public authorities following the Habitat III conference of the United Nations in Quito in 2017. The objective of this article is to show how largely uncontrolled spatial dynamics delay the sustainable development of greater Lomé. To achieve this, this research used quantitative and qualitative approaches based respectively on questionnaire administration and individual interview techniques. In total, 232 landowners and resource persons were interviewed. Field investigations have shown that liberal fixation on land has led to the occupation of unapproved areas and the privatization of administrative reserves. This creates urban instability marked by conflicts between public authorities and populations. This situation, very detrimental to the sustainable city, demonstrates weakened urban governance.